ANALISIS KARAKTER DISIPLIN SISWA KELAS V SDN 112 PEKANBARU - Akpal Pangestu; Erlisnawati; Guslinda (STKIP Subang, 2026)
This study aims to analyze the disciplinary character of fifth-grade students at SDN 112 Pekanbaru and to identify the factors influencing its development. The research employed a qualitative descriptive approach involving the principal, the fifth-grade teacher, and fifth-grade students as research subjects. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing, with data validity ensured through source, technique, and time triangulation. The findings indicate that students’ disciplinary character has developed fairly well, reflected in three main indicators: time discipline, rule compliance, and behavioral discipline. Time discipline is demonstrated through punctual attendance and timely assignment submission; rule compliance is reflected in adherence to school regulations and willingness to accept gradual sanctions; while behavioral discipline is shown through politeness, responsibility, and respect toward teachers and peers. Supporting factors include teacher role modeling, consistent habituation practices, enforcement of school rules, and character-based school programs, whereas inhibiting factors mainly stem from inconsistent discipline practices within the family environment. In conclusion, the disciplinary character of fifth-grade students at SDN 112 Pekanbaru has been developed through continuous habituation and collaboration between school and family, although further reinforcement is needed to transform external compliance into students’ internal awareness.